Can the mini-libraries (mini-libs) be a solution for library users with print disabilities? A case of the North West Province, South Africa. Issue 4 (2nd October 2021) - Kaunda, Neli; Chizwina, Sabelo
Abstract: A library should be accessible and provide inclusive services. This is a challenge for many developing countries. However, with limited funding and infrastructure, there have been concerted attempts to mitigate this challenge. This paper focuses on mini-libs as a possible solution for library users with print disabilities. A case study approach is used to focus on a South African partnership between the North-West University and the North-West Provincial Department of Arts and Culture. Funding was sought to establish and support mini-libs in the North West Province community libraries through a leading South African petroleum company. Using a qualitative approach, the study investigated the implications of establishing mini-libraries (mini-libs) as a possible solution. The main results identified challenges in resource provision, negative attitudes in library staff, and accessibility to the min-libs. Training for both library patrons and library staff is recommended to resolve some of the challenges reported. The paper also recommends that resources be allocated for the mini-libs to be relevant to the library patrons.